Implementation of Sustainability and Green Building Standards in the UAE: An analysis of Relevant Instruments - GOMAA, AMGAD MOHAMED (2017)
At the time green buildings concept is highly required by the buildings’ owners and different authorities and becomes more widespread in order to manage the resources and energy to sustain and reduce the cost of developing and maintaining buildings, and thus save the environment and maximize the economic turnover. Construction contracts should be formed to protect parties including architects, contractors, and building owners, and to define their liabilities and risks. A successful contract should be well formed in order to achieve the target requested by the owner for completing his investment and development on time, within budget, and in accordance to the scope and standards. As an example, it is the role of the architect to plan the orientation of the building to maximize the natural ventilation for better heating and cooling, while the role of the contractor to execute the building in accordance to the design, standards and regulations, and to use recycled raw materials considering the origin and location of delivery along with waste management in addition to his role to maintain adequate documentation in order to obtain “LEED” or “BREEAM” certificate. On the other hand, the tenant who occupies the building is responsible for adequate operation and to maintain the space properly. The aim of this dissertation is to come out with a well formed conditions of contract that manage the owner’s expectations by writing specifically what are the obligations and roles of each party, and the ramifications of not fulfilling the obligations related to designing and constructing green buildings in order to reduce disputes among the parties .